Implementation of Peer Group Support to Improve Mental Health and Resilience in Adolescents Post-Online Learning in Public High Schools - Moh Solehuddin; Nur Faliza; Jenuri Jenuri; Mustangin Mustangin; Yasriuddin Yasriuddin (PT Inovasi Pratama Internasional, 2026)
The transition from emergency remote learning to in-person schooling following the COVID-19 pandemic has left Indonesian high school students confronting substantial mental health vulnerabilities, including elevated stress, anxiety, and diminished resilience. This study investigated the effectiveness of a structured peer group support intervention in improving mental health outcomes and resilience among adolescents in a public senior high school (SMA Negeri) context. Employing a quasi-experimental, non-equivalent control group design, the research involved 218 students (110 in the intervention group, 108 in the control group) from a state high school in East Java, Indonesia. The intervention group participated in an eight-week peer support program comprising weekly group sessions, psychoeducation modules, and guided peer interactions, while the control group received standard school guidance services. Mental health was assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21), and resilience was measured with the Connor-Davidson Resilience Scale (CD-RISC). Data were collected at pre-test, post-test, and an eight-week follow-up, and analyzed using independent and paired sample t-tests, repeated measures ANOVA, and ANCOVA. Results indicated that the intervention group exhibited statistically significant improvements in mental health (reductions in depression, anxiety, and stress) and resilience scores compared to the control group, with medium to large effect sizes (ηp² ranging from .09 to .24). The findings demonstrate that peer group support represents a culturally congruent, scalable, and cost-effective strategy for addressing post-pandemic mental health challenges in Indonesian secondary education settings. The study underscores the critical role of peer relationships in adolescent psychological well-being and provides an evidence-based framework for integrating peer support programs into national school health initiatives.